Evidence Based Education e modelli di valutazione formativa per le scuole - Antonio Calvani; Giuliano Vivanet (LED Edizioni Universitarie, 2014)
Evidence Based Education and School Education Evaluation Models Evidence Based Education (EBE) is emerging as an approach focusing on the problem of reliability in educational research, on its theoretical foundations, and on the relationship between research and decision-making. On the latter, less well known are the implications resulting from it for the development of innovative school evaluation systems based on dynamic methods, and thus differing from static models based on raw data compared to general standards. We shall firstly provide a brief summary of the EBE approach as well as the main research centers and general issues in this field. Then, we will show how notions of feedback and formative assessment, currently recognized as really effective individual learning strategies, can act as reference points for school evaluation and orientation models, by introducing the New Zealand system, developed with the collaboration of John Hattie, one of the most representative of the EBE approach, which suggests to move from a static to a dynamic accountability.